Understanding the biochar's role in ameliorating soil acidity - Ren-yong SHI; Jiu-yu LI; Ni NI; Ren-kou XU (Journal of Integrative Agriculture, 2019)
Extensive acidic soils, which suffer from accelerated soil acidification, are found in southern China. Soil acidity, aluminum toxicity, and nutrient deficiencies severely limited crop productivity in acidic soils. It has been widely reported that crop residue biochars can ameliorate acidic soils and increase crop productivity. Here, we summarized the positive effects and mechanisms involved in the correction of soil acidity, the alleviation of aluminum toxicity and the increase of soil pH buffering capacity by crop residue biochars. The carbonate, oxygen-containing functional groups and silicates in biochars are the major components responsible for their efficacy in amending acidic soils and resisting soil re-acidification. We conclude that application of crop residue biochars may be a better option than traditional liming to ameliorate acidic soils. Nonetheless, further researches into soil acidification are still required to address some issues that are controversial and poorly understood.